2023
DOI: 10.4236/psych.2023.142010
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Emotional Intelligence and Thinking Style in Saudi Residents: A Cross-Sectional Study

Abstract: Background: Emotional Intelligence (EI) and style of thinking (Rational style, RS and Experiential style, ES) are stable constructs that could be used to highlight how we think and behave, which is extremely important, especially in the healthcare sector, as it is complex and human-dependent. This study explored the EI and style of thinking of Saudi residents together with demographic data to see how they could relate and the implications of this on residents and patient safety. Design: This was a cross-sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…EI in this study was found to have a significant negative effect on Neuroticism, where the higher scores of EI, the lower scores of Neuroticism (objective 2), and this is in line with other studies (Bataweel, 2023;Hjalmarsson & Dåderman, 2022). There were no significant differences between gender and EI (objective 2), and this is in line with other studies for nurses (Bataweel, 2023) and for physicians (Bataweel & Ahmed, 2023). However, other studies contrasted this for gender, where one found female nurses to have higher scores in EI than males (Kahraman & Hicdurmaz, 2016), and other studies found males in Radiography to have higher scores than females (McNulty et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…EI in this study was found to have a significant negative effect on Neuroticism, where the higher scores of EI, the lower scores of Neuroticism (objective 2), and this is in line with other studies (Bataweel, 2023;Hjalmarsson & Dåderman, 2022). There were no significant differences between gender and EI (objective 2), and this is in line with other studies for nurses (Bataweel, 2023) and for physicians (Bataweel & Ahmed, 2023). However, other studies contrasted this for gender, where one found female nurses to have higher scores in EI than males (Kahraman & Hicdurmaz, 2016), and other studies found males in Radiography to have higher scores than females (McNulty et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…High social media usage could also be used as a trigger to psychological issues and lower emotional stability. It was found that high social media usages staff had significantly lower scores in all EI components, including self-control (objective 3), and this is in line with other studies, especially with the self-control component (Bataweel & Ahmed, 2023;Jie et al, 2022;Süral et al, 2019) where they used this behavior to escape negative past thoughts and other negative feelings.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…EI was proven to have a positive impact on all desirable behavior for the organization and is strongly linked to the BFI and thinking styles. Open Journal of Nursing Therefore, it is valuable if organizations invest in improving EI in their providers [15]. Even though EI and BFI might be genetic constructs [65], short training, like 1 -3 months, was found to increase EI scores significantly [34] [35], and the training would not change the providers' genetic construct; instead, it would highlight areas for improvement and equip them with appropriate and advantageous coping strategies [82] [83].…”
Section: Discussionmentioning
confidence: 99%
“…Emotional Intelligence (EI) could help in identifying certain behavior aspects that organizations might need to focus on for a healthier workforce [15]. A high score of EI was found to significantly correlate with less stress and burnout, better mental health, better performance and retention, better adjustment with organizational change, less self-harm and more happiness and life flexibility during challenges, more self-control against addiction and safer patient care [16]- [24].…”
Section: Introductionmentioning
confidence: 99%